Thrombosis in renal artery in a newborn. Presentation a review of a case (Colombia Medica, 2009)
This report describes a newborn who presents high pressure values and absence of pulses in inferior extremities in his 4th day of life. Posterior to placement of umbilical arterial catheter, confirming diagnostic of thrombosis in aorta and left renal artery. A gamagraphy with MAG 3 was performed that gave evidence of left renal exclusion and aorta and left renal angioresonance. A management with no fractional heparin and streptokinase during 6 hours was initiated. The compromise in lower extremities was totally recovered, improving presure values in a few days. Following studies of renal function and growth give evidence of left renal artery flow and some function. This report describes an improvement with anticoagulant and thrombolitic treatment of a newborn kidney depite of a prolonged ischemia.